Finite control set model predictive torque control using sliding model control for induction motors - Yanqing Zhang; Zhonggang Yin; Wei Li; Jing Liu; Yanping Xu (CES Transactions on Electrical Machines and Systems, 2021)
Finite control set model predictive torque control (FCS-MPTC) has become increasingly prevalent for induction motors (IM) owing to its simple concept, easy incorporation of constraints and strong flexibility. In traditional FCS-MPTC speed controller design, a classical proportional integral (PI) controller is typically chosen to generate the torque reference. However, the PI controller is dependent on system parameters and sensitive to the load torque variation, which seriously affects control performance. In this paper, a model predictive torque control using sliding mode control (MPTC + SMC) for IM is proposed to enhance the robust performance of the drive system. First, the influence of the parameter mismatches for FCS-MPTC is analyzed. Second, the shortcomings of traditional PI controller are derived. Then, the proposed MPTC + SMC method is designed, and the MPTC + PI and MPTC + SMC are compared theoretically. Finally, experimental results demonstrate the correctness and effectiveness of the proposed MPTC + SMC. In comparison with MPTC + PI, MPTC + SMC has the better dynamic performance and stronger robust performance against parameter variations and load disturbance.